Outcomes of mindfulness-based stress reduction and mindfulness-based cognitive therapy in adults with diabetes: a systematic review - Mason, James; Meal, Andrew; Shaw, Ian; Adams, Gary G. (Gavin Publishers, 2018)
Objectives: Diabetes Mellitus (DM) is a global and progressive chronic medical condition with increasing prevalence and associated costs throughout the world. Psychological problems are common in people with DM and when they co-occur are associated with negative patient and societal outcomes. Mindfulness-Based Stress Reduction (MBSR) and Mindfulness-Based Cognitive Therapy (MBCT) were to be effective in treating a variety of psychological problems in various health conditions. Thus, using MBSR and MBCT in DM patients may help alleviate psychological problems of anxiety and depression and improve glycaemic control as a result. In this systematic review, we investigated the effectiveness of MBSR and MBCT in improving glycaemic control, anxiety and depression in adults with DM. Interventions: Randomised-Controlled Trials (RCTs) and Pilot Studies (RCPS) evaluated the effectiveness of MBSR or MBCT. Electronic searches were carried out of the following databases CINAHL, CENTRAL, EMBASE, MEDLINE, PsycINFO, PubMed, and ongoing clinical trials websites. Main outcomes: This research examined the effectiveness of MBSR and MBCT on depression, anxiety and glycaemic control in adults with T1DM or T2DM. Results: Research evidence has shown that patients with mental illnesses such as schizophrenia and anxiety disorders have a higher risk of developing DM than the general population. Explicitly, evidence indicates that the prevalence of psychological problems is much higher than in the general population and globally, with a two-fold increase in the prevalence of depression and anxiety in DM patients. 3 RCTs and 1 RCPS found a total of 365 participants. Narrative and data synthesis indicated significant reduction in levels of anxiety and depression at short-term and long-term time points. However, no significant effect on glycaemic control was established. MBSR and MBCT are feasible and efficacious methods for depression and anxiety treatment in adults with T1DM or T2DM.